Entrevista a el exdirector D. Jerónimo Morales Barroso - Rodríguez Bravo, Marcos; Rojas Martín, Mª del Rosario (Avances en Supervisión Educativa, 2024)
Interview with the former Principal Mr. Jerónimo Morales Barroso, from Tenerife (Spain)